2022
DOI: 10.3390/healthcare10030553
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Social Interaction and Virtual Connections as Strong Predictors of Wellbeing of Older Adults

Abstract: Socially engaged older adults are less likely to decline in health and happiness and have a higher quality of life. Building upon this premise, examination was conducted on the domains of social determinants of health, specifically the social and community context per Healthy People 2030 objectives. These mechanisms of social interaction, in the form of group activities, community engagement, and virtual interactions via email or text message, were assessed using hierarchical regression analysis to find out th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The social support provided by students can foster emotional health for the isolated, frail, older adult who is no longer at the center of a network of friends and acquaintances. Older adults with social connections have a high quality of life under social support [ 11 ], are motivated to work and engage in social activities, and have an inclusive attitude that promotes a healthy lifestyle [ 12 ]. Hence, they have low risk of conditions such as depression, additive behaviors, or dementia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The social support provided by students can foster emotional health for the isolated, frail, older adult who is no longer at the center of a network of friends and acquaintances. Older adults with social connections have a high quality of life under social support [ 11 ], are motivated to work and engage in social activities, and have an inclusive attitude that promotes a healthy lifestyle [ 12 ]. Hence, they have low risk of conditions such as depression, additive behaviors, or dementia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the relationship between the family and community environment and life satisfaction in older adults has received widespread academic attention [ 9 , 19 ]. Studies have found that an increase in the breadth and depth of family and social networks can enhance life satisfaction among older adults [ 20 , 21 , 22 ]. However, research on the mechanisms of influence between the two is somewhat lacking.…”
Section: Introductionmentioning
confidence: 99%